Orthodox perspectives on mission - Vassiliadis, Petros (Oxford. : : Regnum Books International, 2013)
This volume not only offers a wide-ranging analysis of TTL [Together Towards Life], the new mission affirmation of the World Council of Churches, but explores the century of ecumenical missiology which underpins and informs this ground-breaking text."--
Includes bibliographical references and index.
Keywords: Orthodox Eastern Church -- Missions